Implementation of a monthly individualized learning plan with emergency medicine residents. Issue 4 (2nd December 2021) - Getto, Leila P.; Drake, Joshua; Kern, Alyssa; Fredette, Jenna
Abstract: Objectives: Self‐assessment and self‐directed learning (SDL) are integral to developing competent physicians who are lifelong learners. Individualized learning plans (ILPs) are tools to formalize this process and allow for mentors to guide residents in developing these skills. Pediatric residencies have adopted the ILP process and have demonstrated improvement in resident SDL behavior, but to date there have been no EM residencies to adopt the ILP process into resident education. Methods: The ILP program was designed around three key elements: (1) resident performance of self‐assessment; (2) a collaborative conversation about learning needs and goals; and (3) a shared development of implementation strategies. The program was implemented with 12 PGY1 EM residents in the 2019–2020 academic year. Following an introduction to ILPs during orientation, residents met monthly with program leadership to create and reflect on ILPs. At the conclusion of the academic year, residents were surveyed about their attitude toward the ILP process and SDL. Results: A total of nine residents completed the postimplementation survey. Prior to implementing the ILP program, residents universally reported that they had little to no experience with generating an ILP. Following implementation, 55% of residents described themselves as strong independent learners and 89% wanted to continue the program into their second year. Conclusions: Overall, residents felt that the ILP program helped to focus their goals, monitor their progress, and allowed them to develop a relationship with program leadership.